2020
DOI: 10.1007/s11249-020-01351-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thickness and Particle Size on Tribological Properties of Graphene as Lubricant Additive

Abstract: Increasing studies have demonstrated excellent tribological properties of graphene as lubricant additive. Thus, extended explanations of the relationship between microstructure and tribological properties are needed. This paper reported the effects of thickness and particle size of graphene on its frictional performance, using a ball-on-plate tribotester under reciprocating condition. Graphene with few-layer (G2) or multi-layer (G10) structure was added to PAO4 as lubricant additive. The particle of G10 was fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 46 publications
1
19
0
Order By: Relevance
“…Nearly ∼50% reduction in wear was due to 2 wt % MLG in group III base oil. A similar enhancement in AW performance (∼47%) has been reported by Kong et al 32 for MLG flakes added in PAO 4 base oil. They explored the effect of thickness and size of graphene sheets on the friction performance as an additive in PAO 4 base oil.…”
Section: Atomic Force Microscopysupporting
confidence: 86%
See 1 more Smart Citation
“…Nearly ∼50% reduction in wear was due to 2 wt % MLG in group III base oil. A similar enhancement in AW performance (∼47%) has been reported by Kong et al 32 for MLG flakes added in PAO 4 base oil. They explored the effect of thickness and size of graphene sheets on the friction performance as an additive in PAO 4 base oil.…”
Section: Atomic Force Microscopysupporting
confidence: 86%
“…Some NPs, in particular, having layer-lattice structures transfer the beneficial nanofilm on the surfaces, while hard and spherical NPs work as nanobearings, thereby transforming sliding contact into rolling contact and thus reducing friction and wear. Also, most NPs are chemically inert and relatively less toxic and thus have less environmental implications than conventional additives such as ZDDP and have been reported to offer better fuel efficacy. , In order to cater to the need for new generation machine components mainly for high thermal efficiency, several types of NPs from carbon family-like C 60 (buckyballs), nanographite (NG), nanodiamond, carbon nanotubes (CNTs), graphene, and so forth have been explored. , Especially, since the inception of graphene in 2004 by Geim, various forms of graphene and its chemical derivatives, viz., graphene oxide (GO), reduced graphene oxide (rGO), and chemically modified graphene, have been extensively explored as lubricant additives. Graphene nanoflakes refer to one single layer of atomic carbon (0.34 nm thickness) atoms arranged in a honeycomb 2-D hexagonal lattice structure. Although, in multilayer graphene (MLG), several graphene planes are weakly bonded together through van der Waal forces in the thickness direction .…”
Section: Introductionmentioning
confidence: 99%
“…Graphene shows remarkable tribological properties as solid lubricant and lubricant additives in lubricating oils, owing to its large surface area, weak interlayer interaction, excellent chemical stability, and versatile surface modification, as well as thermal conductivity and heat transfer performance. Especially for the most widely used liquid lubricants, graphene-based additives have been widely reported for the aqueous or oil system, after atom doping or in the form of composites . It has been well-recognized that the tribological performance of the nanolubricants was mainly determined by the following four factors: the micromorphology, , number of layers, size, and surface nature of the graphene.…”
Section: Introductionmentioning
confidence: 99%
“…The smaller size makes the graphene-based lubricant additives easy to be dispersed in the lubricating oils with better stability . The smaller graphene-based lubricant additives also provide more edge-functionalization of polar groups, which is favorable for the formation of a lubricating film on the sliding surfaces, , but goes against the dispersibility in the widely used nonpolar lubricating oils (such as poly-α-olefin (PAO)) and low polar ones (esters). In addition, it has been reported that graphene nanosheets could be ground into smaller pieces during the friction process .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation